2022
DOI: 10.7717/peerj.13387
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory patterns and factors influencing perinatal fatigue among Chinese women from late pregnancy to 6 months after delivery

Abstract: Background Perinatal fatigue among women is related to the clinical outcomes of mothers and infants. Perinatal fatigue changes over time, and the trajectory varies according to the predictors and outcomes of the mothers. This, however, has not been documented in any study. Objectives This study aimed to identify and characterize the trajectory patterns of perinatal fatigue among women from late pregnancy to 6 months after delivery. Methods We used growth mixture modeling to estimate the trajectory of perin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Taylor and Johnson62 found that perinatal fatigue reached the lowest level at 6 months after delivery, in line with our study. In another study, the lowest fatigue score was also observed at 6 months in the ‘perinatal fatigue persistently low’ group 63. This may be because the number of night wakings gradually stabilises at 6 months, thus gradually increasing the sleep duration at night 64.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Taylor and Johnson62 found that perinatal fatigue reached the lowest level at 6 months after delivery, in line with our study. In another study, the lowest fatigue score was also observed at 6 months in the ‘perinatal fatigue persistently low’ group 63. This may be because the number of night wakings gradually stabilises at 6 months, thus gradually increasing the sleep duration at night 64.…”
Section: Discussionmentioning
confidence: 92%
“…In another study, the lowest fatigue score was also observed at 6 months in the 'perinatal fatigue persistently low' group. 63 This may be because the number of night wakings gradually stabilises at 6 months, thus gradually increasing the sleep duration at night. 64 This allows the mother to get better rest, reducing fatigue.…”
Section: Discussionmentioning
confidence: 99%